Technique for quality assessment of external appearance of paint coatings - Логанина, Валентина Ивановна (Technology audit and production reserves, 2014)
The data on the regularities of making an external appearance quality of coatings on a cement substrate has been given. The regularities of changing the surface roughness of cement concrete paint coatings, depending on the rheological properties of paints, cement porosity of the substrate, the way of applying paints, have been determined. The increase of the surface roughness of coatings with decreasing conditional dynamic viscosity of paints has been found out. Based on probabilistic and deterministic approaches the model of external appearance quality of coatings, taking into account the surface porosity of the substrate and the surface tension of paint, has been proposed. It has been suggested assessing the quality of paint coating surfaces by a fractal dimension indicator. The relation between numerical values of the fractal dimension indicator and the quality class of external appearance of coatings has been found. The model of profile length of the coating surface from the D fractal dimension has been proposed.